Adaptation of Teacher Subjective Wellbeing Questionaire (TSWQ) to Turkish: A Validity and Reliability Study - Elif Ergün; Şenay Sezgin Nartgün (Sakarya University Journal of Education)
The aim of this study was to adapt Teacher Subjective Wellbeing Questionnaire which was developed by Renshaw, Long and Cook (2015) to Turkish culture. Data were obtained from 544 teachers working at schools of Ministry of Education. The questionnaire consists of 8 items and 2 factor named School Connectedness and Teaching Efficacy. Explanatory Factor Analyses (EFA) and Confirmatory Factor Analysis (CFA) were executed to test the construct validity of the scale. As a result of the exploratory factor analysis, it was found that scale had a two dimensional structure as in the original scale. Results of CFA indicated that the fit values of the model were acceptable (x²= 56.01, sd= 18, RMSEA= .075, NFI= 0.97, NNFI= 0.96, CFI= 0.98, GFI= .096, AGFI= 0.93, GFI= 0.96, SRMR=0.04). Reliability coefficients of the total scale was .82. According to study findings scale adapted to Turkish culture is a valid and reliable measurement tool for teacher subjective wellbeing.